Humpback whale movements in a narrow and heavily-used shipping passage, Chile - Guzman, Hector M.; Capella, Juan J.; Valladares, Carlos; Gibbons Escobar, Jorge Eduardo; Condit, Richard (My University, 2020)
The Magellan Strait is a narrow passage connecting the Pacific and Atlantic oceans in South America. An average of 2023 ships per year transit this corridor with 80% representing the international fleet. The southwestern part of the Strait in Chile is an important summer feeding area for humpback whales. Considering the risk to whales of feeding among dense ship traffic, the movements of 25 satellite-tagged whales relative to vessel density were analyzed, to provide policy recommendations for protecting the species from vessel collisions. A total of 3694 filtered whale positions from 21 individuals were obtained along the southwest passage. The daily range covered by individual whales was 8.8 km, and <25 km on 90% of all days. Ship density in the same square kilometers where whales were encountered was 0.27 per week, slightly more often than once per month, however this encounter rate varied by 100-fold between individuals, depending on how often animals were in the central shipping lane. One of the tagged whales stopped transmitting and washed up dead suggesting a ship strike. In the last decade, four other humpback whales and three sei whales were killed by probable ship strikes, all near Isla Carlos III, the core of the humpback feeding area. A 10-knot speed restriction and onboard observers are recommended during the five months of maximum whale abundance, applying to all merchant vessels traveling through the Strait, between Cabo Holland and Isla Bonete north of Carlos III Island, for a distance of 28 nautical miles (52 km).
Keywords: whale-vessel collisions; whale satellite tracking; vessel strikes; humpback whale; international maritime organization; chile